Anticancer Activities of Seven Peronemins (A2, A3, B1, B2, B3, C1, and D1) from Peronema canescens Jack: A Prediction Studies - Fikriansyah, Muhammad; Nelson, Nelson; Latief, Madyawati; Tarigan, Indra Lasmana (Chempublish Journal, 2023)
Cancer is one of the leading causes of human death. In 2019, it was reported that cancer was the second (22%) cause of death due to non-communicable diseases in the world's population. Research for alternative anticancer drugs is still being done, including anticancer from plants. One of the plants that have the potential to be developed as an anticancer alternative is the sungkai plant. Sungkai leaves contain many bioactive compounds, one of which is the clerodane-type diterpenoids, peronemins, A2 (1), A3 (2), B1 (3), B2 (4), B3 (5), C1 (6), and D1 (7). The aim of this study was to initial screen the potential of seven Peronemins compounds in Sungkai leaves extract as anticancer candidates. Initial screening was carried out by predicting in-silico anticancer activity of the seven compounds. Dihydrofolate reductase inhibitor (DHFR inhibitor) is one of the anticancer activity screening approaches. DHFR Inhibitor activity from perenomins derivatives with pIC50 values ​​of 0.785 (A2), respectively; 0.785 (A3); 0.799 (B2); 0.799 (B3); 0.799 (C1 and D1). In addition, from compounds 1,2,3,4,5 peronemin derivatives have potential anticancer activity through interaction with the target protein Voltage-gated potassium channel subunit while compounds 6, 7 also have biological activity potential anticancer on target protein Dihydrofolate reductase.